1969
DOI: 10.12669/pjms.303.4798
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an Iec (Information, Education and Communication) Intervention on Key Family Practices of Mothers Related to Child Health in Jamshoro, Sindh

Abstract: Objective: To determine change in practice of mothers having children less than five years of age in five key areas related to child health, growth and development including immunization, feeding during illness, appropriate home treatment for infections and care seeking behavior. Methods: This was a community based interventional study of Information, Education and Communication (IEC) intervention in the UC Jamshoro, Taluka Kotri, district Jamshoro of 15 months duration from March 2011 to June 2012. Ninety fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…Shaikh et al demonstrated in their study in Jamshoro, Pakistan, that educating mothers had resulted in improved immunization of children, improved continued breast feeding during illness and increased ability of mothers to recognize danger signs. They further emphasized that effects of such interventions do not last for long periods and require continued efforts if changes in attitude and behavior are to be sustained [19]. These studies have found results similar to that reported in the current study.…”
Section: Discussionsupporting
confidence: 87%
“…Shaikh et al demonstrated in their study in Jamshoro, Pakistan, that educating mothers had resulted in improved immunization of children, improved continued breast feeding during illness and increased ability of mothers to recognize danger signs. They further emphasized that effects of such interventions do not last for long periods and require continued efforts if changes in attitude and behavior are to be sustained [19]. These studies have found results similar to that reported in the current study.…”
Section: Discussionsupporting
confidence: 87%
“…[9,10] Many different studies have been conducted worldwide to assess the impact of educational intervention on number of health issues which may include the prevalent diseases in a community or in a country. So far in my knowledge very few interventional studies have been conducted in Pakistan while there are many studies conducted worldwide on different diseases and health related problems such as mental health, [11] menstruation, [12] child health, [13] hypertension, [14] diabetes mellitus, [15][16][17] and osteoporosis. [18,19] Trials involving one or more than one methods of health education regarding the disease osteoporosis have shown a significant effect of health education on knowledge as compared to beliefs and habits.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that total 450 responses were correct fill the questioner in which 21.3 recorded with male gender and remaining were females preponderance (78.7%). As for the gender, female preponderance is higher because mothers are the main care giver and more time with their kids than fathers 14 . Most of the parents (44.7%) were reported in age group of 30-39 years.83.6% parents were educated and their source of information was doctors (73.6%).…”
Section: Discussionmentioning
confidence: 99%